USING A PROBLEM-ORIENTED APPROACH TO TRAINING IN THE PROCESS OF CONDUCT OF PRACTICAL TRAINING - Mukhtarova Nargiza Tokhirovna; Yoqubova Guldiyora daughter of Umedjon; Ravshanova Qorako‘z daughter of Uchqun (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Teaching with active and interactive methods is widely introduced into the educational process. Foreign experience shows that at the current stage, integration occurs in the direction of ensuring the competent use of the achievements of pedagogic science in the process of real interaction with students. A teacher of a medical educational institution should have theoretical knowledge and practical skills in the use of various technologies in the educational process. Some solutions to the problem are given in this article.